2023
DOI: 10.21926/obm.neurobiol.2302167
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence of Shared Intentionality: Towards Bioengineering Systems Development

Abstract: This expanded conference paper reports the results of a psychophysiological research study on shared intentionality conducted in 24 online experiments with 405 subjects (208 recipients and 197 contributor-confederates). In this research, we created a bioengineering system for assessing shared intentionality in human groups by modeling mother-neonate dyad properties in subjects during solving unintelligible multiple-choice puzzles. In this model, only the mother (contributor-confederate) knows the correct stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This concise article focuses on the possible impact of external low-frequency oscillations on the synchronization of specific local neuronal networks from peripheral and central nervous subsystems, the self-contained piece of original research on shared intentionality. Our recent studies proposed assessing a cognitive development delay in preverbal children by measuring shared intentionality magnitude [1][2][3][4][5]. This computer-aided method emulated the mother-fetus communication model in a bioengineering system (children over 18 months) for modulating shared intentionality.…”
Section: Empirical Evidence Of Shared Intentionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…This concise article focuses on the possible impact of external low-frequency oscillations on the synchronization of specific local neuronal networks from peripheral and central nervous subsystems, the self-contained piece of original research on shared intentionality. Our recent studies proposed assessing a cognitive development delay in preverbal children by measuring shared intentionality magnitude [1][2][3][4][5]. This computer-aided method emulated the mother-fetus communication model in a bioengineering system (children over 18 months) for modulating shared intentionality.…”
Section: Empirical Evidence Of Shared Intentionalitymentioning
confidence: 99%
“…Growing data from the neuroscience hyperscanning research [6][7][8][9][10][11] showed increased inter-brain synchrony in adult subjects performing similar cognitive tasks without interacting with sensory cues compared to solving these tasks alone. The psychophysiological [5,[12][13][14][15][16] research studies showed empirical evidence of shared intentionality in adult subjects performing similar cognitive tasks without communication. Our hypothesis about the neurobiological processes during shared intentionality argued that this pre-perceptual communication occurs through nonlocal neuronal coupling in an ecosystem that can be described as the mother-fetus communication model [17][18][19].…”
Section: Empirical Evidence Of Shared Intentionalitymentioning
confidence: 99%